Infinite [videorecording (DVD)] - Shorr, Ian; Stein, Todd; Wahlberg, Mark, 1971-; Gregson-Williams, Harry; Ejiofor, Chiwetel; Cookson, Sophie, 1990-; Mantzoukas, Jason; Friend, Rupert; Jones, Toby, 1966-; O'Brien, Dylan, 1991-; Jóhannes Haukur Jóhannesson; Maikranz, D. Eric (David Eric), 1967- (Paramount Pictures, 2023)
Evan McCauley (Mark Wahlberg) is haunted by memories of places he has never been and manifests skills he's never learned. Self-medicated and on the brink of a mental breakdown, a secret group that call themselves "Infinites" come to his rescue, revealing to him that his memories are real - but they are from multiple past lives. Evan must work with the Infinites to unlock answers in his memories that are the key to stopping a madman from destroying humanity.